The Effect of Sports Injuries on the Skill of Self-confidence in Athletes: A Case of King Faisal University, KSA - Al-Salman, Abdulaziz Ali (Journal of Posthumanism, 2025)
This study aimed to investigate the impact of sports injuries on the self-confidence of athletes at King Faisal University, KSA. Self-confidence is a critical psychological factor influencing athletic performance, and understanding its relationship with sports injuries can provide insights into effective mental and physical rehabilitation strategies. With a sample size of 30 athletes from various sports disciplines, the research employed a mixed-methods approach to assess how injuries influence an athlete’s self-confidence levels. Quantitative data were collected through a structured questionnaire, measuring variations in self-confidence before and after injury, while qualitative insights were gleaned from in-depth interviews, exploring athletes’ personal experiences and coping mechanisms. The findings indicate that sports injuries significantly diminish self-confidence, often leading to psychological distress and apprehension about future performance. However, athletes employing effective rehabilitation and psychological resilience strategies demonstrated a capacity to restore and even enhance their self-confidence post-recovery. This study underscores the need for comprehensive support systems, including psychological counseling and tailored rehabilitation programs, to assist athletes in regaining their self-confidence following an injury. The insights call for further research, involving larger cohorts, to generalize findings and develop universal strategies for athlete support post-injury.